Tea Growing and Social Economic Development of Local Communities in Rubanda: A Case Study of Ikumba Sub-County Rubanda District. - Aharimpisya, Janet (Kabale University, 2024)
The purpose of this study was therefore to investigate the effects of tea growing on the social and economic development of local communities in Ikumba sub-county, Rubanda District. The study was guided by specific objectives, which include determining the effect of tea growing on the income levels of local communities, finding out the effect of tea growing on infrastructure development among the local communities, and determining the effect of tea growing on the education levels of local communities in the Ikumba sub-county. The study used a descriptive cross-sectional research design utilizing both qualitative and quantitative data collection and analysis methods. Using simple random and purposive sampling techniques, a total of 133 respondents were selected to participate in the study. Questionnaires, interviews, and documentary methods of data collection were used in this study. The study discovered a significant positive relationship between tea growing and the income levels of local communities in the Ikumba sub-county (p = 0.01, r =.530**), indicating that tea growing has a significant association with income levels. The study survey findings on the effect of tea growing on income levels of local communities, majority of the respondents 70 (53%) agreed that tea is seen as a major source of household income to a few tea farmers in Ikumba sub-county since tea is a major export cash crop and holds potential to improve the living standards of smallholder farmers in Ikumba sub-county with (Mean= 2.78, SD= 1.804) implying that tea is a major source of income to the households in Ikumba sub-county. It was found that most of the participants 70 (53%) indicated that there has been the release of road rehabilitation funds in tea estate areas which has led to infrastructure development with (Mean= 3.10, SD= 0.. 791). It was concluded that the majority of the participants 80 (60%) strongly agreed that tea factories were setting up primary and secondary schools to provide quality education for the children in the area in Ikumba sub-county thus reducing the illiteracy rate and giving jobs to educated people in the area and also with still majority agreeing that local community has got money to pay school fees as indicated with (Mean= 3.41, SD = 0.854). It was suggested that tea be grown alongside other food crops to reduce famine in families who have grown tea on all of their land, and thus famine. If this is done, the number of stunted children may be reduced.